The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/nn.3040
|View full text |Cite
|
Sign up to set email alerts
|

Selective control of inhibitory synapse development by Slitrk3-PTPδ trans-synaptic interaction

Abstract: Balanced development of excitatory and inhibitory synapses is required for normal brain function, and their imbalance may underlie pathogenesis of neuropsychiatric disorders. Compared with many identified trans-synaptic adhesion complexes that organize excitatory synapses, little is known about organizers specific for inhibitory synapses. Here we report Slit and NTRK-like family member 3 (Slitrk3) as a postsynaptic adhesion molecule that selectively regulates inhibitory synapse development via trans-interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
305
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(328 citation statements)
references
References 51 publications
(93 reference statements)
21
305
1
1
Order By: Relevance
“…A recent expression screen for synaptogenic proteins uncovered several LRR proteins that have synaptogenic activities (Linhoff et al, 2009). One synaptogenic protein identified in this study was Slitrk2, which was shown to induce both excitatory and inhibitory presynaptic differentiation (Linhoff et al, 2009;Takahashi et al, 2012). Taken together, these observations indicate that a subset of Slitrks function in promoting synapse formation and maturation.…”
Section: Slit and Trk-like Familysupporting
confidence: 52%
See 4 more Smart Citations
“…A recent expression screen for synaptogenic proteins uncovered several LRR proteins that have synaptogenic activities (Linhoff et al, 2009). One synaptogenic protein identified in this study was Slitrk2, which was shown to induce both excitatory and inhibitory presynaptic differentiation (Linhoff et al, 2009;Takahashi et al, 2012). Taken together, these observations indicate that a subset of Slitrks function in promoting synapse formation and maturation.…”
Section: Slit and Trk-like Familysupporting
confidence: 52%
“…Other Slitrks induce both excitatory and inhibitory synapse differentiation. Slitrk3-deficient mice exhibit a specific decrease in inhibitory synapse number and function and an increase in seizure susceptibility (Takahashi et al, 2012). The authors of this latter study demonstrated that all six Slitrks mediate trans-interaction with receptor protein tyrosine phosphatase-δ (PTPδ), an action that is responsible for the inhibitory-specific synaptogenic activities of Slitrks, at least, in artificial synapse formation assays.…”
Section: Slit and Trk-like Familymentioning
confidence: 96%
See 3 more Smart Citations